The role of universities in the development of public sector innovations - Polbitsyn, Sergei N. (The Innovation Journal, 2021)
Studies on public sector innovation often treat this type of innovation as something that emerges within public sector organizations. However, innovation theory argues that external sources of innovation are more fruitful sources of ideas. We claim that universities must be treated as a mandatory element in public sector innovation. This paper is aimed at clarifying the place of public sector innovation in the classification of innovations currently used in the literature. It also seeks to conceptualize an approach for future research on the topic. Our primary goal is to identify the role of different actors in the development of public sector innovation. We analyze the advantages and disadvantages of different forms of university involvement in public sector innovation. The paper consists of two parts. The first defines concepts of innovation in general and public sector innovation viewed as a variation on social innovation. The second is dedicated to an analysis of the experience of Russian universities in enhancing collaboration between actors in the public innovation system.
Keywords: Asie; Réservé UdeM; Rôle des universités